2021
DOI: 10.20944/preprints202101.0112.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Future Changes in Precipitation Extremes Over East Africa Based on CMIP6 Projections

Abstract: This paper presents an analysis of precipitation extremes over the East African region. The study employs six extreme precipitation indices defined by the Expert Team on Climate Change Detection and Indices (ETCCDI) to evaluate possible climate change. Observed datasets and CMIP6 simulations and projections are employed to assess the changes during the two main rainfall seasons of March to May (MAM) and October to December (OND). The study evaluated the capability of CMIP6 simulations in reproducing the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For characterizing daily features of precipitation and temperature extreme events over Cameroon, we analysed seven extreme event indices defined by the Expert Team on Climate Change Detection and Indices (ETCCDI, Sillmann et al, 2013; Zhang et al, 2011). The choice of the seven indices is based on the objective of characterizing how extreme events currently affecting Cameroon's socio‐economic sectors will respond in a warmer world, and they have been widely used for this purpose in many previous studies (e.g., Akinsanola et al, 2020a, 2020b, 2020c; Ayugi et al, 2021, 2022; Chou et al, 2009; Dosio et al, 2021; Haensler et al, 2013; Sillmann et al, 2013). The indices' identity, their names, definition and units are summarized in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…For characterizing daily features of precipitation and temperature extreme events over Cameroon, we analysed seven extreme event indices defined by the Expert Team on Climate Change Detection and Indices (ETCCDI, Sillmann et al, 2013; Zhang et al, 2011). The choice of the seven indices is based on the objective of characterizing how extreme events currently affecting Cameroon's socio‐economic sectors will respond in a warmer world, and they have been widely used for this purpose in many previous studies (e.g., Akinsanola et al, 2020a, 2020b, 2020c; Ayugi et al, 2021, 2022; Chou et al, 2009; Dosio et al, 2021; Haensler et al, 2013; Sillmann et al, 2013). The indices' identity, their names, definition and units are summarized in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that while the region is expected to warm rapidly, projections on precipitation show an increase in rainfall over the study domain (Shongwe et al, 2011;Ongoma et al, 2018;Osima et al, 2018;Ayugi et al, 2021). The expected recovery in precipitation is likely to offset the impacts of warming, which could adversely impact agriculture due to the sharp increase in evapotranspiration and subsequent increase in drought and aridity.…”
Section: Temperature Projections For the 21 St Centurymentioning
confidence: 95%
“…Also, Ukkola et al ( 2020) noted an increase in meteorological drought duration over southern Africa, Guinea and the northern African coasts in the CMIP5 and CMIP6 ensembles. Ayugi et al (2021a) found an increase in CDD, along with an intensification of extreme precipitation over East Africa, while Moon and Ha (2020) noted a thermodynamically driven increase in precipitation rates over the monsoon regions.…”
Section: Projection Of Future Precipitation Characteristicsmentioning
confidence: 99%
“…More recently, CMIP6 simulations have been investigated in terms of mean precipitation change at continental scale (Almazroui et al 2020) and for southern Africa (Sian 2021), and by extreme events over East Africa (Ayugi et al 2021a). In addition, Moon and Ha (2020) and Ukkola et al (2020) investigated future characteristics of (global) monsoon precipitation and meteorological droughts, respectively.…”
Section: Introductionmentioning
confidence: 99%